Alopecia and pet: a case report - Eduardo Cukierman; Thiago Zinsly Sampaio Camargo; Laís Pereira Bueno Millan; Marianna Ribeiro de Menezes Freire; Lucas Franco Mendes Carneiro; Renata Dejtiar Waksman (Einstein (São Paulo), 2022)
ABSTRACT Dermatophytoses are fungal infections affecting the skin and cutaneous annexes. This clinical case report describes a 7-year-old girl with Kerion celsi, a severe manifestation of Tinea capitis. The patient presented with painful edematous crusty scalp lesions and alopecia, which required surgical debridement and long-term antifungal treatment. Culture of samples collected from scalp and arm skin lesions (patient and patient’s mother respectively) were positive for Trichophyton mentagrophytes. The family owned a pet guinea pig. This particular dermatophytosis is easily transmitted from guinea pigs to humans, with some studies showing up to 34.9% prevalence of Trichophyton mentagrophytes infection in these animals.